Accounting for the reproduction of forest resources of Ukraine during and after wartime - Танасієва, Марина (Journal of Innovations and Sustainability, 2022)
The purposeof the article is the formation of theoretical foundations for the development of accounting in forestry enterprises in response to the challenges of the concept of sustainable development, in terms of the development of accounting support for the reproduction of forest resources of Ukraine for the purpose of their preservation and restoration during and after the wartime.
Keywords: облік; економіка природокористування; лісове господарство; розвиток бухгалтерського обліку